Brain transcriptomics reveal the activation of neuroinflammation pathways during acute Orientia tsutsugamushi infection in mice - Liang, Yuejin; Aditi,; Onyoni, Florence; Wang, Hui; Gonzales, Casey; Sunyakumthorn, Piyanate; Wu, Ping; Samir, Parimal; Soong, Lynn (Frontiers in Immunology, 2023)
Scrub typhus, an acute febrile illness caused by Orientia tsutsugamushi (Ot), is prevalent in endemic areas with one million new cases annually. Clinical observations suggest central nervous system (CNS) involvement in severe scrub typhus cases. Acute encephalitis syndrome (AES) associated with Ot infection is a major public health problem; however, the underlying mechanisms of neurological disorder remain poorly understood. By using a well-established murine model of severe scrub typhus and brain RNA-seq, we studied the brain transcriptome dynamics and identified the activated neuroinflammation pathways. Our data indicated a strong enrichment of several immune signaling and inflammation-related pathways at the onset of disease and prior to host death. The strongest upregulation of expression included genes involved in interferon (IFN) responses, defense response to bacteria, immunoglobulin-mediated immunity, IL-6/JAK-STAT signaling, and TNFA signaling via NF-κB. We also found a significant increase in the expression of core genes related to blood-brain barrier (BBB) disruption and dysregulation in severe Ot infection. Brain tissue immunostaining and in vitro infection of microglia revealed microglial activation and proinflammatory cytokine production, suggesting a crucial role of microglia in neuroinflammation during scrub typhus. This study provides new insights into neuroinflammation in scrub typhus, highlighting the impact of excessive IFN responses, microglial activation, and BBB dysregulation on disease pathogenesis.